Human Suffering during Pandemic Covid 19 in Eschatological Perspective - Purwoko, Paulus Sentot; Wahyuni, Sri; Sahertian, Novita Loma; Ming, David (Technium BioChemMed, 2021)
The COVID-19 outbreak has become a pandemic in almost all countries in the world. This pandemic made scientists think hard to find the cause of the virus and at the same time struggle to find the right medicine and vaccine. This pandemic has caused panic in the world community, including Indonesia. Because the emergence of this virus is very dangerous and can be deadly as well as its rapid spread, making people think that this virus is a kind of divine punishment on humans, some even ask whether this virus is part of the signs that the end of time has arrived. This panic made it difficult for religious leaders to answer questions and respond to wild statements. Therefore the authors see Covid 19 in an eschatological perspective towards the end of time. The author will use a descriptive method to provide an overview of the existing problems, the objectives of writing this scientific paper are: First, to find out in detail about Covid 19 which has become a pandemic in the world and especially in Indonesia. Second, to provide an explanation regarding eschatological understanding, an explanation of this subject will describe the verses related to the subject of eschatological teaching towards the end of time. Third, to explain the relationship between the current epidemic and the eschatological understanding, and how it implies our actions in dealing with the plague